Locally produced blended cement suits for oilwell cementing job - Samsuri, Ariffin; Shahrudin, Shahrin (1994)
With the same chemical compounds as the imported class G cement used for the oil and gas wells cementing jobs; further suitability studies on the physical properties of pulverize fly ash cement were carried out to determine its real potential. Compressive strength, free water, thickening time and fluid loss tests were carried out according to API Specification 10. Samples were prepared with oil well additives and were conducted at simulated reservoir condition at 8000 feet. Comparison results with class G cement proved that blended cement suits to be used for oil well cementing job.